2016
DOI: 10.1149/2.0551608jes
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Stability of Poly(Phenylene Oxide) Based Anion Exchange Membranes Containing Imidazolium Cations

Abstract: Two modified imidazole bases (1-heptyl-2-methyl-imidazole and 1-dodecyl-2-methyl-imidazole) were synthesized, each with a long alkyl chain (7 or 12 carbon) attached to the N-3 position. Anion exchange membranes (AEMs) were prepared with imidazolium cations derived from these bases that were either grafted directly onto the benzyl position of poly(phenylene oxide) (PPO) or affixed to the PPO using a hexyl spacer chain. First, we reacted 1-methylimidazole with brominated PPO and with PPO with a hexyl spacer chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…14, However, it has been shown that quaternary ammonium-based AEMs are sensitive toward Hofmann elimination 20,41 and direct nucleophilic elimination reactions 42,43 that result in loss of ion exchange capacity (IEC) and ionic conductivity. To resolve the stability problem inherent to quaternary-ammonium-group-containing AEMs, several alternative cations, including imidazolium, 41,44,45 benzimidazolium, 3,45,46 guanidinium, 15,47,48 phosphonium 8,9,49 and metal cations 50,51 have been proposed and investigated. Phosphonium-based AEMs were investigated by Gu et al 52 Gu et al attached benzyl-tris(2,4,6-trimethoxyphenyl) phosphonium (TTMPP + ) onto polysulfone backbone to make AEMs, and found them to be alkaline stable; There was no ionic conductivity fade after immersion in 1M KOH for 30 days at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14, However, it has been shown that quaternary ammonium-based AEMs are sensitive toward Hofmann elimination 20,41 and direct nucleophilic elimination reactions 42,43 that result in loss of ion exchange capacity (IEC) and ionic conductivity. To resolve the stability problem inherent to quaternary-ammonium-group-containing AEMs, several alternative cations, including imidazolium, 41,44,45 benzimidazolium, 3,45,46 guanidinium, 15,47,48 phosphonium 8,9,49 and metal cations 50,51 have been proposed and investigated. Phosphonium-based AEMs were investigated by Gu et al 52 Gu et al attached benzyl-tris(2,4,6-trimethoxyphenyl) phosphonium (TTMPP + ) onto polysulfone backbone to make AEMs, and found them to be alkaline stable; There was no ionic conductivity fade after immersion in 1M KOH for 30 days at room temperature.…”
mentioning
confidence: 99%
“…The solution was titrated with 0.1 M potassium thiocyanate (0.1 M KSCN, standard solution) until the color changed from a light orange to a medium-dark orange color (equivalence point). A control sample was prepared by mixing 20 mL of 1 M NaNO 3 with 5.0 mL of 0.1 M AgNO 3 and 2-3 drops of 11 wt% of Fe(NO 3 ) 3 . The control was also titrated with 0.1 M KSCN and the difference in volume used to titrate the control solution and the sample solution was used for calculating the IEC (see Equation 1):…”
mentioning
confidence: 99%
“…The chemical and mechanical stability and high conductivity of SEBS-based AEMs make them promising separator candidates for electrode-decoupled RFBs. There is a growing interest in using anion exchange membranes (AEMs) as separators in alkaline membrane fuel cells (AMFCs) [1][2][3] and in other energy conversion and storage systems such as redox flow batteries (RFBs), 4-6 alkaline water electrolyzers (AWEs) 7-9 and reverse electrodialysis (RED) cells. …”
mentioning
confidence: 99%
“…There is a growing interest in using anion exchange membranes (AEMs) as separators in alkaline membrane fuel cells (AMFCs) [1][2][3] and in other energy conversion and storage systems such as redox flow batteries (RFBs), [4][5][6] alkaline water electrolyzers (AWEs) [7][8][9] and reverse electrodialysis (RED) cells. 10 RFBs are promising candidates for large-scale energy storage systems since the capacity, power and energy density parameters can be designed independently and easily modified even after installation.…”
mentioning
confidence: 99%
“…The currently used ion‐exchange polymer electrolytes respectively are proton‐exchange membranes (PEMs) and anion‐exchange membranes (AEMs) . Because commercial PEMs are expensive and it is difficult to overcome their tendency to corrode, AEMs have recently attracted much research attention AEMs have recently attracted much research attention . For example, Xiong et al synthesized quaternary poly(vinyl alcohol) AEM (QAPVA) and obtained the OH − conductivity of 7.34 × 10 −3 S cm −1 but did not study thermal stability, alkaline stability, and other properties of this membrane.…”
Section: Introductionmentioning
confidence: 99%